Galaxy halo truncation and giant arc surface brightness reconstruction in the cluster MACSJ1206.2-0847 - Eichner, Thomas; Zitrin, Adi; Bartelmann, Matthias (Arxiv, 2013)
In this work we analyze the mass distribution of MACSJ1206.2-0847, especially focusing on the halo properties of its cluster members. The cluster appears relaxed in its X-ray emission, but has significant amounts of intracluster light which is not centrally concentrated, suggesting that galaxy-scale interactions are still ongoing despite the overall relaxed state. The cluster lenses 12 background galaxies into multiple images and one galaxy at $z=1.033$ into a giant arc and its counterimage. The multiple image positions and the surface brightness distribution (SFB) of the arc which is bent around several cluster members are sensitive to the cluster galaxy halo properties. We model the cluster mass distribution with a NFW profile and the galaxy halos with two parameters for the mass normalization and extent of a reference halo assuming scalings with their observed NIR--light. We match the multiple image positions at an r.m.s. level of $0.85\arcsec$ and can reconstruct the SFB distribution of the arc in several filters to a remarkable accuracy based on this cluster model. The length scale where the enclosed galaxy halo mass is best constrained is about 5 effective radii -- a scale in between those accessible to dynamical and field strong lensing mass estimates on one hand and galaxy--galaxy weak lensing results on the other hand. The velocity dispersion and halo size of a galaxy with $m_{\rm 160W,AB}=19.2$ or $M_{\rm B,Vega}=-20.7$ are $σ=150 \rm kms^{-1}$ and $r≈ 26± 6 \rm kpc$, indicating that the halos of the cluster galaxies are tidally stripped. We also reconstruct the unlensed source (which is smaller by a factor of $\sim5.8$ in area), demonstrating the increase of morphological information due to lensing and conclude that this galaxy has likely star--forming spiral arms with a red (older) central component.